(untitled) (Gayana Botánica, 2004)
We present a checklist of vascular plants for Pali Aike National Park, one of the world southernmost protected areas, located in Chilean Patagonia. The park conserves remnants of the Patagonian steppe ecosystem of the eastern side of the Straits of Magellan. 164 vascular species were recorded, from 44 families and 106 genera, comprising one Pteridophyta, one Gnetophyta, 114 Magnoliopsida and 48 Liliopsida. Exotic species make up 11% of the flora.